Vilém Flusser, Popular Culture and the Bossa Nova - Duarte, Rodrigo (Scenari, 2021)
Vilém Flusser, who lived in Brazil for over thirty years, became a very interested observer of several aspects of the life and the culture of the country. In opposition to many foreigners who visited Brazil in the previous times, Flusser was not well impressed by the nature of the country and his benevolent judgement was directed solely to its culture, which he evaluated as a very curious mixture of European, African and indigenous elements. He was always aware of the possible syntheses that could arise from all these influences, having a special passion for the Afro-Brazilian cultural phenomena. Among these he emphasized the role of the Brazilian popular music, specially the one of the Bossa Nova, that synthesized Afro-Brazilian rhythms with impressionist and jazzy harmony and modernistic poetry.